2015
DOI: 10.2174/1570180812666150529204909
|View full text |Cite
|
Sign up to set email alerts
|

A Series of 2,4(1H,3H)-Quinazolinedione Derivatives: Synthesis and Biological Evaluation as Potential Anticancer Agents

Abstract: A series of 6,7-disubstituted-3-{2-[4-(substituted)piperazin-1-yl]-2-oxoethyl}quinazoline-2,4(1H,3H)-dione derivatives (7-34) were synthesized and their structures were elucidated on the basis of analytical and spectral (UV, IR, 1 H-NMR, 13 C-NMR and MS) data. These synthesized compounds were evaluated for their in vitro cytotoxicities against a panel of three human cancer cell lines. According to the cytotoxicity screening results, 3-{2-[4-(4-chlorobenzyl)piperazin-1-yl]-2-oxoethyl} quinazoline-2,4(1H,3H)-dio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Quinazoline-2,4(1H,3H)-dione constitutes an important class of nitrogen-containing heterocycles with biological activities that find a large number of applications as pharmaceuticals. [316][317][318][319] The synthesis of quinazoline-2,4(1H,3H)-dione derivatives starting from non-toxic, low cost and readily available substrates such as CO 2 and 2-aminobenzonitrile is of great interest and constitutes an environmentally friendly process with 100% atom efficiency and an alternative route to the use of toxic phosgene, carbamates, 320 anthranilic acids with urea, 321,322 potassium cyanate and chlorosulfonyl isocyanate. 319 A new, straightforward and overall green synthetic route of quinazoline-2,4(1H,3H)-dione in the presence of DBU has been reported.…”
Section: Other Formation Of C-n Bondmentioning
confidence: 99%
“…Quinazoline-2,4(1H,3H)-dione constitutes an important class of nitrogen-containing heterocycles with biological activities that find a large number of applications as pharmaceuticals. [316][317][318][319] The synthesis of quinazoline-2,4(1H,3H)-dione derivatives starting from non-toxic, low cost and readily available substrates such as CO 2 and 2-aminobenzonitrile is of great interest and constitutes an environmentally friendly process with 100% atom efficiency and an alternative route to the use of toxic phosgene, carbamates, 320 anthranilic acids with urea, 321,322 potassium cyanate and chlorosulfonyl isocyanate. 319 A new, straightforward and overall green synthetic route of quinazoline-2,4(1H,3H)-dione in the presence of DBU has been reported.…”
Section: Other Formation Of C-n Bondmentioning
confidence: 99%
“…It is well evident that quinazolinedione derivatives possess anticancer activity. Akgun et al reported the synthesis of quinazolinedione derivatives and their antiproliferative activities against three different cancer cell lines, and the results showed that some derivatives exhibited cytotoxicity below 10 µM [ 19 ]. Compound 3 ( Figure 1 ) and related compounds, which are 3-substituted-2,4-quinazolinedione derivatives, are patented for their highly potent cytotoxicity against human ovarian cancer (SKOV3) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is one of the fatal diseases, which is characterized by uncontrolled cell division leading to metastasis and invasion into adjacent tissues. Synthesizing new anticancer agents with less side effects and increased selectivity is still a developing area of interest in medicinal chemistry [ 1 ]. A significant portion of the improved clinical outcomes in cancer can be attributed to refined chemotherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%